2020
DOI: 10.5194/npg-27-307-2020
|View full text |Cite
|
Sign up to set email alerts
|

Correcting for model changes in statistical postprocessing – an approach based on response theory

Abstract: Abstract. For most statistical postprocessing schemes used to correct weather forecasts, changes to the forecast model induce a considerable reforecasting effort. We present a new approach based on response theory to cope with slight model changes. In this framework, the model change is seen as a perturbation of the original forecast model. The response theory allows us then to evaluate the variation induced on the parameters involved in the statistical postprocessing, provided that the magnitude of this pertu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Lang et al ( 2020 ) have recently shown that sliding training period windows that incorporate at least some historical data have an advantage over the conventional approach. In an interesting proof-of-concept, Demaeyer and Vannitsem ( 2020 ) investigate a technique based on response theory to incorporate small model changes into the estimation of post-processing coefficients.…”
Section: Univariate Post-processingmentioning
confidence: 99%
“…Lang et al ( 2020 ) have recently shown that sliding training period windows that incorporate at least some historical data have an advantage over the conventional approach. In an interesting proof-of-concept, Demaeyer and Vannitsem ( 2020 ) investigate a technique based on response theory to incorporate small model changes into the estimation of post-processing coefficients.…”
Section: Univariate Post-processingmentioning
confidence: 99%
“…The forecasts are obtained by a chain of ensemble numerical simulations. The 10-member reforecasts of the PEARP ensemble NWP (Descamps et al, 2015;Boisserie et al, 2016) are downscaled by the SAFRAN system (Durand et al, 1999) to obtain a meteorological forcing adjusted in elevation. The Crocus multilayer snowpack model, part of the S2M modelling chain (Vernay et al, 2019), is forced by these forecasts to provide ensemble simulations of HN, accounting for all the main physical processes explaining the variability in HN for a given precipitation amount, namely the dependence of falling snow density on meteorological conditions, the mechanical compaction over time depending on snow weight, the microstructure and wetness of the snow, a possible surface melting, and so on.…”
Section: Datamentioning
confidence: 99%
“…Time-adaptive training based on operational systems is an alternative to favour the homogeneity of the data set. Although new theories are emerging to face the challenge of model evolutions (Demaeyer and Vannitsem, 2020), several consistent recent studies show that the length of the calibration period is more critical than the strict homogeneity of data sets to forecast rare events (Lang et al, 2020;Hess, 2020). In the case of HN forecasts from EMOS (Nousu et al, 2019), even a 4-year calibration period was detrimental for the reliability of severe snowfall events compared to a longer heterogeneous reforecast.…”
Section: Limitations For Operational Perspectivesmentioning
confidence: 99%
“…Time adaptative training based on operational systems is an alternative to favour the homogeneity of the dataset. Although new theories are emerging to face the challenge of model evolutions (Demaeyer and Vannitsem, 2020), several consistent recent studies show that the length of the calibration period is more critical than the strict homogeneity of datasets to forecast rare events (Lang et al, 2020;Hess, 2020). In the case of HN forecasts from EMOS (Nousu et al, 2019), even a 4-year calibration period was detrimental for the reliability of severe snowfall events compared to a longer heterogeneous reforecast.…”
Section: Limitations For Operational Perspectivesmentioning
confidence: 99%